Involvement of autophagy in mesaconitine-induced neurotoxicity in HT22 cells revealed through integrated transcriptomic, proteomic, and m6A epitranscriptomic profiling - Lin, Xiaohuang; Zhang, Jian; Wu, Zekai; Shi, Yuan; Chen, Mengting; Li, Maodong; Hu, Hong; Tian, Kun; Lv, Xiaoqi; Li, Chutao; Liu, Yang; Gao, Xinyue; et al. (Frontiers in Pharmacology, 2024)
Mesaconitine (MA), a diester-diterpenoid alkaloid extracted from the medicinal herb Aconitum carmichaelii, is commonly used to treat various diseases. Previous studies have indicated the potent toxicity of aconitum despite its pharmacological activities, with limited understanding of its effects on the nervous system and the underlying mechanisms. In this study, HT22 cells and zebrafish were used to investigate the neurotoxic effects of MA both in vitro and in vivo, employing multi-omics techniques to explore the potential mechanisms of toxicity. Our results revealed that MA treatment inhibited the neural development of zebrafish and induced structural and functional damage to mitochondria in HT22 cells, accompanied by an upregulation of mRNA and protein expression related to autophagic and lysosomal pathways. Furthermore, MeRIP-seq showed that the expression of autophagy-related genes correlated with m6A modification after MA treatment. In addition, we identified METTL14 as a potential regulator of m6A methylation in HT22 cells after MA treatment. In conclusion, our study has contributed to a thorough mechanistic elucidation of the neurotoxic effects caused by MA, and has provided valuable insights for optimizing the rational utilization of traditional Chinese medicine formulations containing aconitum in clinical practice.